Seeking attention: an investigation of salesperson influence strategies used while selling to small retailers. Issue 2 (2nd April 2016) - Nanarpuzha, Rajesh; Noronha, Ernesto
Abstract : The use of influence strategies is an integral component of the salesperson's role, while selling to retailers. However, it remains a chronically under-researched area, particularly so in emerging markets, which are distinct in terms of retail formats and salesperson challenges. In this study, we investigate influence strategies used by salespersons for selling to retailers in the dominant small retail format in India. Using a combination of observation techniques and in-depth interviews, we allow salesperson influence strategies at play to emerge. In comparison to extant literature, we find evidence for both universality and specificity in the types of influence strategies used at small retail. We identify 'share of counter' as a unique small retail phenomenon, potentially requiring a specific set of salesperson influence strategies to succeed. Based on this, a modified typology of salesperson influence strategies, specific to small retail, is proposed. We conclude with a discussion of theoretical and managerial implications for emerging markets, and offer suggestions for future research.